Peningkatan Perilaku Anti Korupsi Melalui Metode Story Telling - Lestari, Dwi Puji (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2018)
The purpose of this research was to determinate the proccess of implementation of story telling metode to increase behavior of anti-corruption in Group B Az Zahra Kebayoran Baru South of Jakarta. This research is an action research which refers to the model of a classroom Action Research Kemmis and Mc. Taggart. The subject of this research are children in Group B Az Zahra Kebayoran Baru South of Jakarta there are 16 children, who consist of  6 girls and 10 boys.  The steps of this research : 1) Planing (2) Action (3) Observation (4) Reflection. Data analysis used quantitative and qualitative. Data analysis qualitative used  Miles and  Hubberman model. This research do in two cycles, there are cycle I and II. The end result of the overall analysis of the data is the percentage in 88,05% cycles II which showed from pre-cycle is 41,23% up to cycles I 72,32%